Finding a Style for Presenting Shakespeare on the Japanese Stage - Minami, Ryuta (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
Japanese productions of Shakespeare’s plays are almost always discussed with exclusive focus upon their visual, musical and physical aspects without any due considerations to their verbal elements. Yet the translated texts in the vernacular, in which most of Japanese stage performances of Shakespeare are given, have played crucial part in understanding and analysing them as a whole. This paper aims to illuminate the importance of the verbal styles and phraseology of Shakespeare’s translated texts by analysing Nakayashiki Norihito’s all-female productions of Hamlet (2011) and Macbeth (2012) in the historical contexts of Japanese Shakespeare translation.